Tough adhesion enhancing strategies for injectable hydrogel adhesives in biomedical applications - Ouyang, Chenguang; Yu, Haojie; Wang, Li; Ni, Zhipeng; Liu, Xiaowei; Shen, Di; Yang, Jian; Shi, Kehang; Wang, Huanan (Advances in colloid and interface science, 2023)
Injectable hydrogel adhesives have gained widespread attention due to their ease of use, fast application time, and suitability for minimally invasive procedures. Several biomedical applications depend on tough adhesion between hydrogel adhesives and tissues, including wound closure and healing, hemostasis, tissue regeneration, drug delivery, and wearable electronic devices. Compared with bulk hydrogel adhesives formed ex situ, injectable hydrogel adhesives are more difficult to achieve strong adhesion strength due to a further balance of cohesion and adhesion while maintaining their flowability. In this review, the critical principles in designing tough adhesion of injectable hydrogel adhesives are summarized, including simultaneously enhancing their intrinsic interfacial toughness (Γ0inter) and mechanical dissipation (ΓDinter). Thereafter, various design strategies to enhance the Γ0inter and ΓDinter are discussed and evaluated respectively, involving multiple noncovalent/covalent interactions, topological connections, and polymer network structures. Furthermore, targeted biomedical applications of injectable hydrogel adhesives for specific tissue needs are systematically highlighted. In the end, this review outlines the challenges and trends in producing next-generation multifunctional injectable hydrogels for both practical and translational applications. [Display omitted] •General design principles for integrating strong interfacial linkages and tough dissipative hydrogel matrices.•Different strategies for enhancing the intrinsic interfacial toughness (Γ0inter) and the mechanical dissipation (ΓDinter).•Several biomedical applications of injectable hydrogel adhesives targeted to specific tissue adhesion needs.•The challenges and trends in producing next-generation multifunctional injectable hydrogel adhesives.